"Yo te estoy ayudando; estoy aprendiendo también/I am helping you; I am learning too:" A bilingual family's community of practice during home literacy events. (June 2015) - Baird, Ashley Simpson; Kibler, Amanda; Palacios, Natalia
This case study examines one Honduran immigrant family's community of practice during home literacy events. Data include field notes and audio and video recordings from six weeks of in-home observations. Coding and discourse analysis are used to analyse talk-in-interaction in order to understand how the family engages in literacy events. Family discourse reveals patterns of speech according to the language of narrative texts, shared strategy use between mother and child, and the influence of an older sibling. Through the exploration of these patterns, this study documents the multidirectional influence of one family's community of practice where family members are able to leverage their linguistic and/or literate strengths to construct meaning mutually during literacy events. This study provides evidence for the benefits of encouraging bilingual families to include various family members in literacy events as well as to interact with texts in all of the languages spoken in the home. Further implications for practice and avenues for future research are discussed.